Rules for ghosting ebook A novel. - Shore, Shelly Jay (2024)
NATIONAL BESTSELLER • To save his family's failing funeral home—and his own chance at a queer love story—a reluctant clairvoyant must embrace the gift he long ignored in this poignant and warmhearted debut. “For top-notch drama, this year’s medal goes to Rules for Ghosting. . . . Here, actual ghosts haunt the quiet and tender moments, and it’s the scenes at family holidays that leave you rattled and gasping.”— The New York Times Book Review (“One of the Best Romance Novels of 2024”) Ezra Friedman sees ghosts, which made growing up in a funeral home complicated. It might have been easier if his grandfather’s ghost didn’t give him scathing looks of disapproval as he went through a second, HRT-induced puberty, or if he didn’t have the pressure of all those relatives—living and dead—judging every choice he makes. It’s no wonder that Ezra runs as far away from the family business as humanly possible. But when the floor of his dream job drops out from under him and his mother uses the family Passover seder to tell everyone she’s running off with the rabbi’s wife, Ezra finds himself back in the thick of it. With his parents’ marriage imploding and the Friedman Family Memorial Chapel on the brink of financial ruin, Ezra agrees to step into his mother’s shoes and help out . . . which means long days surrounded by ghosts that no one else can see. And then there’s his unfortunate crush on Jonathan, the handsome funeral home volunteer . . . who just happens to live downstairs from Ezra’s new apartment . . . and the appearance of the ghost of Jonathan’s gone-too-soon husband, Ben, who is breaking every spectral rule that Ezra knows. Because Ben can speak. He can move. And as Ezra tries to keep his family together and his heart from getting broken, he realizes that there’s more than one way to be haunted—and more than one way to become a ghost.